TANGGUNGJAWAB PELAKU USAHA ATAS INFORMASI YANG BENAR DAN JELAS ATAS PRODUK SUSU KENTAL MANIS MENURUT UU NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Steven Salim; A.M Tri Anggraini (Fakultas Hukum Universitas Tarumanagara, 2021)
Some people are unable to fulfill their food needs to fulfill their children's nutrition completely. People generally choose to buy affordable food to buy. SKM products provided by business actors whose product content contains very high sugar with this content will cause obesity in the community. The purpose of this thesis is to find out the responsibility of the sweetened condensed milk business actors in the distribution of their products according to Law no. 8/1999 and what is the form of BPOM supervision of the circulation of sweetened condensed milk that provides protection to consumers according to the Consumer Protection Law. Therefore, responsibility and honesty become one of the main obligations for business actors in running their business. With the existence of this responsibility of Business Actors, it is expected to build public trust as consumers in consuming the products of Business Actors. In fact, not all SKM business actors carry out their responsibilities in trading their products in the community. Food content that is not good for consumption every day and lack of information on SKM is a form of neglect of consumer rights that often occurs in society. This action poses a security threat to consumer rights in terms of obtaining clear information regarding the content of food traded by business actors.